2021
DOI: 10.1109/access.2021.3102223
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning-Based Automatic Modulation Classification With Blind OFDM Parameter Estimation

Abstract: Automatic modulation classification (AMC) is an essential factor in dynamic spectrum access to fulfill the spectrum demand of 5G wireless communications for achieving high data rate and low latency. Many deep learning (DL)-based AMC methods have achieved improved accuracy performance for classifying analog modulation schemes, single-carrier-based modulation schemes, and multi-carrier signals using several DL architectures such as the convolutional neural network (CNN) and long-short term memory (LSTM). However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In [ 90 ], a CNN-based MC is studied in order to classify SC and OFDM systems with varying symbol lengths. The majority of older DL-based MC algorithms misinterpreted OFDM-based signals with varying OFDM usable symbol lengths.…”
Section: Artificial Intelligence-based Approach To MCmentioning
confidence: 99%
See 2 more Smart Citations
“…In [ 90 ], a CNN-based MC is studied in order to classify SC and OFDM systems with varying symbol lengths. The majority of older DL-based MC algorithms misinterpreted OFDM-based signals with varying OFDM usable symbol lengths.…”
Section: Artificial Intelligence-based Approach To MCmentioning
confidence: 99%
“…However, this technique has good classification accuracy for the normalized carrier frequency offset of range . In [ 90 ], a CNN-based MC is studied to classify modulation format for OFDM systems in the presence of CFO. FFT window banks (FWB) are utilized as input to the CNN model to estimate the length of an OFDM symbol.…”
Section: Artificial Intelligence-based Approach To MCmentioning
confidence: 99%
See 1 more Smart Citation
“…The FB-AMC makes feature extraction and classification. In order to extract features, expert systems carefully extract various manual features, such as wavelet-based features [9], instantaneous features [10], and statistical features [3], [11].…”
Section: Introductionmentioning
confidence: 99%
“…In Park et al (2021), the authors propose a deep learning-based automatic modulation classification system to classify higherorder OFDM modulations, 64 OFDM to 512 OFDM, at an SNR value of 20 dB. The results obtained are quite low in a classic deep learning manner, as the authors also showed, obtaining an accuracy below 30%.…”
Section: Introductionmentioning
confidence: 99%